Exploration of teaching method incorporating ideological elements for the cutting-edge technology of cyberspace security - Aiqun HU; Guyue LI; Linning PENG; Tao LI (网络与信息安全学报)
The teaching method was explored incorporating ideological elements for the advanced technology of cyberspace security.The teaching content of this course is constituted of six aspects,i.e.,quantum communication,public key infrastructure,physical layer security,blockchain,trusted computing and privacy protection.Apart from teaching the related technologies,the remarkable achievements and efforts of Chinese scientists were shown and the future work was indicated.Students are grouped to do literature research,expand their knowledge,exchange the learning experience and explore the law of scientific research in these new aspects.Students can not only absorb the knowledge of cutting-edge technology,but also learn the method and spirit to address scientific problems.A useful reference for education and teaching method of course ideological for graduate students was provided.